The transcriptome of the mosquito Aedes fluviatilis (Diptera: Culicidae), and transcriptional changes associated with its native Wolbachia infection. (December 2017) - Caragata, E.; Pais, F.; Baton, L.; Silva, J.; Sorgine, M.; Moreira, L.
Abstract Background Wolbachia is a bacterial endosymbiont that naturally infects a wide range of insect species, and causes drastic changes to host biology. Stable infections ofWolbachia in mosquitoes can inhibit infection with medically important pathogens such as dengue virus and malaria-causingPlasmodium parasites. However, some nativeWolbachia strains can enhance infection with certain pathogens, as is the case for the mosquitoAedes fluviatilis, where infection withPlasmodium gallinaceum is enhanced by the nativew FluWolbachia strain. To better understand the biological interactions between mosquitoes and nativeWolbachia infections, and to investigate the process of pathogen enhancement, we used RNA-Seq to generate the transcriptome ofAe. fluviatilis with and withoutWolbachia infection. Results In total, we generated 22, 280, 160 Illumina paired-end reads fromWolbachia -infected and uninfected mosquitoes, and used these to make ade novo transcriptome assembly, resulting in 58, 013 contigs with a median sequence length of 443 bp and anN50 of 2454 bp. Contigs were annotated through local alignments using BlastX, and associated with both gene ontology and KEGG orthology terms. Through baySeq, we identified 159 contigs that were significantly upregulated due toWolbachia infection, and 98 that were downregulated. Critically, we saw no changes to Toll or IMD immune gene transcription, but did see evidence thatw Flu infection altered the expression of several bacterial recognition genes, and immune-related genes that could influencePlasmodium infection.w Flu infection also had a widespread effect on a number of host physiological processes including protein, carbohydrate and lipid metabolism, and oxidative stress. We then compared our data set with transcriptomic data for otherWolbachia infections inAedes aegypti, and identified a core set of 15 gene groups associated withWolbachia infection in mosquitoes. Conclusions While the scale of transcriptional changes associated withw Flu infection might be small, the scope is rather large, which confirms that nativeWolbachia infections maintain intricate molecular relationships with their mosquito hosts even after lengthy periods of co-evolution. We have also identified several potential means through whichw Flu infection might influencePlasmodium infection inAe. fluviatilis, and these genes should form the basis of future investigation into the enhancement ofPlasmodium byWolbachia .